Visual perception in fencing: Do the eye movements of fencers represent their information pickup? - Furley, P.; Memmert, D.; Heller, C. (Attention, Perception, & Psychophysics, 2010)
The present study examined whether results of athletes` eye movements while they observe fencing attacks reflect their actual information pickup by comparing these results with others gained with temporal and spatial occlusion and cuing techniques. Fifteen top-ranking expert fencers, 15 advanced fencers, and 32 sport students predicted the target region of 405 fencing attacks on a computer monitor. Results of eye movement recordings showed a stronger foveal fixation on the opponent`s trunk and weapon in the two fencer groups. Top-ranking expert fencers fixated particularly on the upper trunk. This matched their performance decrements in the spatial occlusion condition. However, when the upper trunk was occluded, participants also shifted eye movements to neighboring body regions. Adding cues to the video material had no positive effects on prediction performance. We conclude that gaze behavior does not necessarily represent information pickup, but that studies applying the spatial occlusion paradigm should also register eye movements to avoid underestimating the information contributed by occluded regions.